Nodular fasciitis: A diagnostic challenge - Sumitoj Singh; Surinder Paul; Kunal Dhall; Sudhir Khichy (Wolters Kluwer Medknow Publications, 2013)
Nodular fasciitis is a rare benign soft tissue tumor. The similarity in the cytological appearance of nodular fasciitis to that of pleomorphic adenoma makes it difficult to diagnose preoperatively that adds to its peculiarity. We report here a case of a middle-aged female with swelling in the neck that was diagnosed as pleomorphic adenoma on cytology. Surgical excision of the swelling was done and histopathological examination revealed it to be nodular fasciitis. This case is presented to highlight the challenge of correctly diagnosing nodular fasciitis.